Pengaruh Belief Dan Self Confidence Terhadap Kemampuan Pemecahan Masalah Matematika - Sri Widiani; M. Habib Husnial Pardi (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
This study aims to determine the effect of belief and self confidence on the ability to solve mathematical problems of grade VIII MTs students. Darul Mahmudien Nw Montong Gamang. This research is a research using a quantitative approach with ex post facto research type.The population in this study was grade VIII MTs. Darul Mahmudien Nw Montong Gamang students totaling 100 students with a sample of 80 students . The variables of this study are belief and self confidence as independent variables and students' mathematical problem solving ability as dependent variables. The data collection techniques used were questionnaires to measure belief and self-confidence and tests to measure students' mathematical problem-solving abilities . Data analysis uses multiple linear regression analysis, before the analysis test is carried out, prerequisite tests are carried out, namely normality tests, linearity tests, multicollinearity tests, heteroscedasticity tests. The results showed that there was an influence between belief and self-confidence on students' mathematical problem solving ability by 88.6%.